Constructing the Purposes of Punishment in the National Criminal Code: Weaving a Prophetic Basis for Transcendent Justice - Sahran Hadziq; Muhamad Syamsudin; Aroma Elmina Martha (Kosmik Hukum, 2026)
The reform of the criminal law in Indonesia through Law Number 1 of 2023 concerning the National Criminal Code (National Criminal Code) has marked a fundamental paradigm shift, especially related to the expansion of the principle of legality and the formulation of penal objectives. This shift indicates the inclusion of "values that live in society" as one of the parameters of criminal law enforcement, which inherently opens the space for interpretation for spiritual and transcendent dimensions in determining the purpose of punishment. This research aims to analyze the problems contained in the construction of the purpose of the National Criminal Code by examining the underlying value of justice and analyzing it based on prophetic foundations to knit transcendent justice. This research uses normative legal research methods supported by secondary data as well as legislative, philosophical and conceptual approaches. The data was collected by conducting a literature study and analyzed through qualitative descriptive methods. The results of this study show that the National Criminal Code has adopted local values, but the potential "value of belief" that refers to Divine or God power has not been explicitly articulated as a strong normative foundation. The prophetic foundation, which emphasizes the ethical-transcendent dimension in law, offers a doctrinal reconstruction to systematically integrate Divine values for the purpose of punishment, not as a theologization of law, but as an affirmation of ratio legis that goes beyond mere utilitarianism. This research argues that the revitalization of prophetic law can enrich the criminal justice discourse in Indonesia, encourage more humanistic, proportionate criminal practices, and rooted in universal moral principles that are believed to come from transcendent sources, to achieve comprehensive justice based on the One Godhead.